Foreign Flow And Transaction Volume Of State-Owned Enterprise Shares In Response To The Announcement Of The Establishment Of Danantara: Event Study - Nurmi Nurmi; Ismail Badollahi; A. Ifayani Haanurat (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes the response of the Indonesian capital market to the announcement of the establishment of Danantara as a national sovereign wealth fund using a comparative quantitative approach and event study method. The focus of the study is on changes in foreign flow and the volume of transactions of strategic state-owned enterprises on the Indonesia Stock Exchange. Secondary data was obtained from ten strategic state-owned enterprises with an observation period before and after the announcement in February 2025. The results show a significant difference in the trading volume of strategic SOE stocks after the establishment of Danantara. In addition, foreign selling experienced a significant change, while foreign buying did not show a significant difference. These findings indicate that the announcement of Danantara's formation was perceived as important information by the market and responded to in the short term, mainly through stock trading activities, while foreign investors tended to be more cautious in adjusting their investment decisions